Pengaruh Store Atmosphere Dan Experiential Marketing Terhadap Keputusan Pembelian Makanan Dan Minuman Angkringan Pada Selebar Cafe And Resto Kabupaten Lebong - Effriando, Millean; Irwanto, Tito; Kurniawan, Kimas (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The thing that must be considered in attracting consumers' interest so that they decide to buy is that the seller must be able to sell a good impression, such as by creating a good store atmosphere and experiential marketing. This study aims to determine the influence of store atmosphere and experiential marketing on purchasing decisions for angkringan food and drinks at Selebar Cafe and Resto in Lebong Regency. The sample in this study was 70 customers at Selebar Cafe and Resto in Lebong Regency. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. Store atmosphere has a significant effect on consumer purchasing decisions at Selebar Cafe and Resto in Lebong Regency, this is proven by the results of the t test showing that the t count is greater than t table (4.008 > 1.667) and the significant value is 0.000 < 0.05, meaning it is rejected and accepted. . Experiential marketing has a significant influence on consumer purchasing decisions at Selebar Cafe and Resto in Lebong Regency, this is proven by the results of the t test showing the t count is greater than t table (3.640 > 1.667) with a significant value of 0.001 < 0.05 meaning Ho is rejected and Ha is accepted. Store atmosphere (X1 ) and Experiential marketing (X2 ) together have a significant effect on consumer’s purchasing decisions (Y) at Selebar Cafe and Resto in Lebong Regency, this is proven by the F test showing the value of Fcount> Ftable (19.212 > 3.13) with a value The significance of 0.000 is smaller than 0.05. The results of the multiple regression have the equation Y = 13.309 + 0.304 ( ) + 0.396 ( ) + e, because the direction of the regression is positive it can be interpreted that if the store atmosphere and experiential marketing increase then purchasing decisions at Selebar Cafe and Restaurants in Lebong Regency will also increase.